Attachment style and occurrence of intimate partner violence in women - Blazevska, Vesna; Jovanovska Stojanovska, Mirjana; Stojmanovska, Katica; Naumovska, Andromahi; Sopronov, Aleksej; Joncheska, Mila (My University, 2023)
The purpose of this research was to contribute to the literature regarding intimate partner violence and women's attachment style. According to the results obtained, intimate partner violence at least occurs among women who have a secure attachment style, followed by women who have a preoccupied affective attachment style. The highest level of violence in the relationship is reported by women who have an avoidant attachment style, and a somewhat lower level of violence is reported by women with a fearful attachment style. 115 women aged 18 to 65 participated in the research. The average age of the respondents is 35.7 years. Of them, 61.10% are married, and 29.90% are in an intimate relationship with a permanent partner, and the average duration of the relationship is 12.5 years. Regarding the level of education, 55.30% have completed secondary school, and 44.70% have higher education. According to employment status, 64.90% are employed and 35.10% are unemployed. All respondents are of Macedonian nationality and Orthodox religion. The results indicate that the existence of a negative image of the partner appears as a factor of occurrence of intimate partner violence.
Keywords: attachment; women; intimate partner violence